Appendectomy in management of malrotation of gut is it necessary? - Eti Sthapak; Pujna Kanneganti; Vijai Datta Upadhyaya; Basant Kumar; Nishant Agarwal; Ashwini Mishra (Journal of Indian Association of Pediatric Surgeons, 2023)
Introduction: Malrotation is a congenital anatomical anomaly that affects the normal positioning of the intestines. Traditional management of malrotation, as described by Ladd, consists of detorsion of the volvulus if present, division of Ladd's bands, widening of the mesenteric root, proper positioning of the small and large bowels, and a prophylactic appendectomy. This study was done to determine whether appendectomy should be an integral part of the Ladds procedure or if it can be avoided. Materials and Methods: This retrospective observational study was conducted in one pediatric surgical unit in the tertiary care center of North India. All the cases of malrotation of the gut managed from January 2008 to December 2018 were reviewed. The details of the patients were recovered from the electronic data recording system of the hospital and manual operation theater records. The cases that have a follow-up of <5 years were not included in the study. The details were charted in an Excel Sheet for the analysis. No statistical test was performed because there was no event in patients in whom prophylactic appendectomy was not done. Results: The data analysis revealed that a total of 66 malrotation patients were managed during this period, those who fulfilled the inclusion criteria. Among 66 cases included in the study, in 41 cases, prophylactic appendectomy was done, whereas in the rest 25, prophylactic appendectomy was not done. During the follow-up, none of the patients in whom the appendix was preserved presented with signs or symptoms related to appendicitis or any other complications. Conclusion: Ladds procedure without appendectomy can be performed in view of the potential use of the appendix in the future, and with the fact that in the current era of advanced medicine, appendicitis can be diagnosed early due to the advancement of imaging and better record keeping.